Can simulation tasks reproduce the taekwondo match physiological responses? - Herrera-Valenzuela, T.; Zapata-Bastias, J.; Guajardo-Medrano, M.; Pons-Vargas, G.; Valdés-Badilla, P.; Ferreira da Silva Santos, J.; Garcia-Hermoso, A.; López-Fuenzalida, A.; Franchini, E. (Archives of Budo, 2018)
Background and Study Aim: Using specific training methods is an important aspect in the preparation of taekwondo athletes. The purpose of the present study is the knowledge about physiological responses, during three different training protocols and official taekwondo matches.